2008
DOI: 10.1007/s11663-008-9202-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Straight Nozzles on Fluid Flow in Mold and Billet Quality

Abstract: Flux entrainment defects in a billet mold with two straight nozzles (outer radius of 60 mm, S60, and 73 mm, S73, and same interior radius of 36 mm) are studied using mathematical simulations and experimental techniques including particle image velocimetry (PIV), tracer injection, and water-oil modeling. Experimental findings indicated that using either of these nozzles at the deepest position of 135 mm (measured from the nozzle tip to the meniscus level) induces a flow near the meniscus, characterized by low t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 16 publications
1
29
0
Order By: Relevance
“…Using the straight SEN, the level fluctuation is less than 1 mm and the velocity magnitude is far from a reasonable interval. One of the reasons for the weak and calm top free surface characteristics is that the use of two nozzles per mold for uniform steel feeding which can reduce the impact caused by molten steel injection, and meanwhile a few publications 9,21) have suggested that the flow near the meniscus is characterized by a low turbulence.…”
Section: Top Free Surface Characteristicsmentioning
confidence: 99%
“…Using the straight SEN, the level fluctuation is less than 1 mm and the velocity magnitude is far from a reasonable interval. One of the reasons for the weak and calm top free surface characteristics is that the use of two nozzles per mold for uniform steel feeding which can reduce the impact caused by molten steel injection, and meanwhile a few publications 9,21) have suggested that the flow near the meniscus is characterized by a low turbulence.…”
Section: Top Free Surface Characteristicsmentioning
confidence: 99%
“…3(d)) where there is an ascending flow to the bath top in the side of the inner mould radius that coincides with results previously presented in a water model. 24) A feasible explanation for the braking effects of both cases is the existence of large buoyancy forces induced by the temperature gradients and the downwards shearing stresses produced by the pulling speed or casting speed of the shell. This later effect is particularly effective along the mould walls as can be seen in Figs.…”
Section: Model Descriptionmentioning
confidence: 99%
“…Generally speaking these changes lead to stronger stirring conditions of the melt at meniscus level. Using a water model and PIV measurements, Torres-Alonso et al 24) found that this narrower gap and the step of the lower ring of nozzle S-73 (see Fig. 1(e)), work synergistically to induce a channelling flow which alters the flow significantly.…”
Section: Model Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is most important in thin slab funnel type molds, which operate at high casting speeds in confined volumes. Controlling turbulence is also important in order to avoid (1) mold flux entrainment which can transform to slivers in the final product 1,2) (2) to avoid meniscus instability, 3,4) (3) to evenly distribute heat transfer for uniform shell growth 5) and (4) to attain steady flow conditions. Some slab casting submerged nozzle designs induce strong meniscus instability and high amplitude oscillations of liquid steel in the mold.…”
Section: Introductionmentioning
confidence: 99%